A SYNTATICAL ANALYSIS OF PHRASES USED IN JOSH GROBAN SONG LYRICS - Daulay, Sholihatul Hamidah; Dalimunte, Muhammad; Ningrum, Diah Widya (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
This study is about a syntactic analysis on sentences in the song lyrics of Josh Groban by using tree diagram theory. Thus, the aims of this study are (1) To find out the types of the phrases used in Josh Groban song lyrics (2) To find out the sentence patterns used in Josh Groban song lyrics. The object of this study is Josh Groban song lyrics which entitled “You Raise Me Up”. The method of this study is qualitative analysis. The technique of collecting the data is by using 3 steps. The 3 steps are: (1) preparing and organizing, (2) coding, and (3) representing the data. Finally, the findings of this study are as follows; (1) there are 3 types of phrases, they are 7 Noun Phrase (NP), 9 adverbial phrases (AP), and 9 verb phrases (VP). (2) There are 3 sentence patterns in Josh Groban song lyrics, they are; (1) S = N+VP (2) S1+Conj.+S2 (S1 = N+V, S2 = N+VP) (3) S1+Conj.+S2 (S1 = N+VP, S2 = N+VP)